Analisis Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Cetakan Continuous Form melalui Kepercayaan Merek (Studi pada Percetakan Jadi Jaya Group, Semarang) - Citra, Tamara; Santoso, Suryono Budi (Diponegoro Journal of Management, 2016)
This study aimed to analyze the effect of product quality and brand image on purchasing decisions continuous form printing with using brand trust as mediator variable study on consumers Jadi Jaya Group, Semarang. The quality of continuous form products is to be considered consumers in making a purchase at Jadi Jaya Group. The strategy used by Jadi Jaya Group to maintain brand image is new innovations with printed paper-based Security Printing design that makes the company different from competitors and increase brand trust.This study used non-probability sampling is used for judgmental sampling. Data were collected from 197 respondents selected using criteria that should have made a purchase of continuous form at least twice. The method analysis used in this research was Maximum Likelihood test using the program of AMOS version 21.0.The results show that the product quality and brand image has positive influence on brand trust. But, brand trust did not positive influence on purchasing decisions. Then, product quality and brand image has positive influence on purchasing decisions continuous form at Jadi Jaya Group, Semarang.